2022
DOI: 10.1167/iovs.63.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Macular Choroidal Thickness and the Risk of Referable Diabetic Retinopathy in Type 2 Diabetes: A 2-Year Longitudinal Study

Abstract: Purpose The purpose of this study was to evaluate the associations between choroidal thickness (CT) and the 2-year incidence of referable diabetic retinopathy (RDR). Methods This was a prospective cohort study. Patients with type 2 diabetes in Guangzhou, China, aged 30 to 80 years underwent comprehensive examinations, including standard 7-field fundus photography. Macular CT was measured using a commercial swept-source optical coherence tomography (SS-OCT) device (DRI O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In terms of the proportional increase in choroidal structure, we demonstrate 11.54% increase in LA, 7.91% increase in SA, 10.26% increase in TCA, and 1.05% increase in CVI over 12 months in the RLRL group as compared with the control group. Given the fact that previous studies have demonstrated that the choroid was 16% thinner among the patients who developed diabetic retinopathy in comparison with who did not in a 2-year follow-up study 40 and 32% thinner among those who developed macular atrophy in comparison with who did not among treatment-naive neovascular age-related macular degeneration patients in an 18month follow-up study, 41 an overall 10% increase in LA and TCA observed after RLRL therapy would likely provide significant clinical benefits to other ocular diseases such as diabetic retinopathy and age-related macular degeneration if a similar level of increase in choroidal thickness and lumen area can be achieved in both children and adults.…”
Section: Discussionmentioning
confidence: 97%
“…In terms of the proportional increase in choroidal structure, we demonstrate 11.54% increase in LA, 7.91% increase in SA, 10.26% increase in TCA, and 1.05% increase in CVI over 12 months in the RLRL group as compared with the control group. Given the fact that previous studies have demonstrated that the choroid was 16% thinner among the patients who developed diabetic retinopathy in comparison with who did not in a 2-year follow-up study 40 and 32% thinner among those who developed macular atrophy in comparison with who did not among treatment-naive neovascular age-related macular degeneration patients in an 18month follow-up study, 41 an overall 10% increase in LA and TCA observed after RLRL therapy would likely provide significant clinical benefits to other ocular diseases such as diabetic retinopathy and age-related macular degeneration if a similar level of increase in choroidal thickness and lumen area can be achieved in both children and adults.…”
Section: Discussionmentioning
confidence: 97%
“…Further, our previous longitudinal studies of the same population have revealed an accelerated decline trend of macular CT with the progression of diabetes in two years follow-up, however, these studies adjusted HTN as a confounder or excluded participants with uncontrolled HTN 19,28 . Given the potential pathological impact of HTN on the choroid, we herein considered BP as an independent impact factor and adjusted other possible confounders, nding that stage 2-HTN was associated with a faster macular CT decline rate, especially in males, patients with higher BMI, HbA1C, and shorter duration of diabetes.…”
Section: Comparison To Previous Studiesmentioning
confidence: 98%
“…A high-resolution SS-OCT device equipping with a max scanning speed of 100000 A-scans/s and a wavelength of 1050 nm scanning light source was used for choroidal imaging (DRI OCT Triton; Topcon, Tokyo, Japan). The speci c methodology has been elaborated in our previous study 19,20 . Brie y, the macular area was scanned by a 3D Macular Cube 7 × 7 mm scan mode, with a scan density of 512 Ascans × 512 B-scans.…”
Section: Swept-source Oct (Ss-oct) Imaging and Ct Measurementsmentioning
confidence: 99%
“…There was a certain relationship between DR and choroidal thickness (CT) (8). Research conducted by Wang et al (9) revealed that CT plays a crucial role in the development of DR. Optical coherence tomography (OCT), widely recognized as a valuable noninvasive imaging technique, can be utilized for choroid imaging (10). OCT-derived CT has been proposed as a quantitative index for evaluating choroidal structure and function.…”
Section: Introductionmentioning
confidence: 99%